Legal Analysis of the Grounds and Mechanisms for the Dismissal of the President and/or Vice President in Indonesia - Timomor, Adensi; Pangalila, Theodorus; Supit, Brain Fransisco (Technium Social Sciences Journal, 2026)
The objective of this study is to analyze the grounds and mechanisms for the dismissal of the President and/or the Vice President prior to the expiration of their term of office. The method employed in this research is normative legal research. The findings indicate that the dismissal of the President and/or the Vice President may be based on evidence of legal violations as stipulated in Article 7 of the 1945 Constitution of the Republic of Indonesia, or on the ground that the officeholder no longer fulfills the constitutional requirements to serve as President and/or Vice President. The legal mechanism for dismissal begins with the House of Representatives (DPR) expressing its opinion, followed by a petition submitted by the DPR to the Constitutional Court to adjudicate that opinion. If the Constitutional Court determines that the DPR’s opinion is legally substantiated, the DPR may then proceed to propose the dismissal of the President and/or the Vice President. The interpretation suggesting that if either the President or the Vice President is to be dismissed, both must be removed on the basis that they constitute a “single ticket” is erroneous, as the term “single ticket” is not stipulated in the Constitution. The phrase “and/or” placed between the words “President and Vice President” clearly indicates that “and” functions as a conjunction denoting joint responsibility, whereas “or” distinctly separates the two offices, namely, the President and the Vice President, depending on which individual has committed the alleged legal violation. Thus, the word “or” signifies that either the President or the Vice President may be dismissed during their tenure if proven to have violated the law. Liability in this context may apply individually or jointly. In other words, unless it is proven that both have violated the Constitution or committed acts prohibited by it, dismissal should apply only to the individual who has committed the violation; however, if both are proven to have violated the Constitution, they must be dismissed jointly from their respective offices.